Reliability and Validity of the Turkish Version of the ABILHAND Questionnaire in Rheumatoid Arthritis Individuals, Based on Rasch Analysis - Bilge BAŞAKCI ÇALIK,; Elif GÜR KABUL,; Murat TAŞÇI,; Suat EREL,; İbrahim Engin ŞİMŞEK,; Pervin DEMİR,; Veli ÇOBANKARA, (Archives of Rheumatology, 2019)
Objectives: This study aims to assess the reliability and validity of the Turkish version of the ABILHAND questionnaire in individuals with rheumatoid arthritis (RA) [ABILHAND-RA (TR)] using the Rasch analysis. Materials and methods: A total 90 individuals (15 males, 75 females; mean age 51.8±10.9 years; range, 20 to 65 years) diagnosed as RA according to the criteria of the American College of Rheumatology were included. The ABILHAND-RA (TR) was used to determine manual ability, while disease activity was evaluated by the use of Disease Activity Score 28 (DAS28). Jamar hand dynamometer and pinch-meter were used to examine grip and pinch strength of the participants. Nine Hole Peg Test (NHPT) and Duruoz Hand Index (DHI) measured hand disability level. Nottingham Health Profile (NHP) was used to assess quality of life. ABILHAND-RA (TR) results were analyzed using the Rasch analysis method. Results: Item 20 was excluded from the 27-item ABILHAND-RA (TR) as 96% of the individuals rated this item as “easy”. The new set of 18 items (7 subtests and 11 items) were found to sustain item invariance and fit to the Rasch model. Significant relationships were found between ABILHAND-RA (TR) and DAS28, bilateral grip strength, NHPT dominant side results, DHI, and NHP. Conclusion: Turkish version of the ABILHAND-RA was found to be clinically valid, reliable, and sensitive enough to be used in clinical evaluations, rehabilitation interventions, and for progression follow-up in individuals with RA.